Pengaruh Media Pembelajaran Kotak Kartu Misterius (KOKAMI) Terhadap Keterampilan Menulis Teks Fabel Siswa Kelas VI di SDN 48 Cakranegara - Amini, Azizah; Ide Bagus Kade Gunayasa; Husniati (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The problem that occurs in class VI of SDN 48 Cakranegara is that teachers rarely use learning media in learning Indonesian, especially in fable text material, the teacher only explains the lesson by lecturing and then gives assignments that make students less enthusiastic in learning. This study aims to determine the effect of the mysterious card box learning media (kokami) on the writing skills of fifth grade students at SDN 48 Cakranegara”. The type of research used in this study is a quantitative research type of experiment. The technique used in collecting data in this research is test and observation. Data analysis used SPSS to test for homogeneity, test hypotheses, and test for normality. The results of this study are that at the homogeneity test stage, a significance (sig.) of 0.858 > 0.05 was obtained, which indicates homogeneous data, while the normality test obtained a significance of 0.136 > 0.05 for the Kolmogorov-Smirnov normality test while the Shapiro-Wilk test was 0.161 > 0 .05 which indicates the data is normally distributed. While the hypothesis test obtained a significance of 0.020 <0.05 which indicates that there is an influence of kokami media on students' writing skills of fable texts. Based on the results of the research that has been done, it can be concluded that the kokami media has an effect on the writing skills of the sixth grade students of SDN 48 Cakranegara.